2016
DOI: 10.1111/imm.12674
|View full text |Cite
|
Sign up to set email alerts
|

Elevated systemic glutamic acid level in the non‐obese diabetic mouse is Idd linked and induces beta cell apoptosis

Abstract: Although type 1 diabetes (T1D) is a T-cell-mediated disease in the effector stage, the mechanism behind the initial beta cell assault is less understood. Metabolomic differences, including elevated levels of glutamic acid, have been observed in patients with T1D before disease onset, as well as in pre-diabetic non-obese diabetic (NOD) mice. Increased levels of glutamic acid damage both neurons and beta cells, implying that this could contribute to the initial events of T1D pathogenesis. We investigated the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Administration of glutamate has been shown to induce adiposity and impair glycemic control in rodents [ 70 , 71 ]. Mechanically, the elevated glutamic acid level was found to induce pancreatic β cell apoptosis through GLT1 [ 36 , 72 ]. Previous studies also revealed a link between gut microbiome and glutamate metabolism [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of glutamate has been shown to induce adiposity and impair glycemic control in rodents [ 70 , 71 ]. Mechanically, the elevated glutamic acid level was found to induce pancreatic β cell apoptosis through GLT1 [ 36 , 72 ]. Previous studies also revealed a link between gut microbiome and glutamate metabolism [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to high-sucrose induced diabetes is also mapped to chromosome 11 (Figure 6a) and genes for impaired b-cell function under a high-sucrose environment was localized to the central and distal segments of chromosome 11 (Figure 6b) 75 . In this region, a susceptibility locus for type 1 diabetes, Idd4, was mapped by genome scanning and congenic mapping in the NOD mice 71,[79][80][81] , suggesting the presence of a common susceptibility gene for both type 1 and type 2 diabetes in this region.…”
Section: Shared Susceptibility Between Type 1 and Type 2 Diabetesmentioning
confidence: 99%
“…The results showed that the glutamate level in copper-laden HLD hepatocytes was significantly higher than that in the shNC cells. An abnormal increase in glutamate activates the signaling pathway of downstream ROS, causing oxidative damage, and can eventually lead to the death of hepatocytes ( Banday and Lejon, 2017 ). After GDD therapy, glutamate levels in cells tended to be normal, indicating that the protective effect of GDD on HLD may be associated with glutamate metabolism.…”
Section: Discussionmentioning
confidence: 99%